Implementasi Peraturan Nagari No 05 Tahun 2015 Tentang Penertiban Ternak Lepas Di Kenagarian IV Koto Hilie Kecamatan Batang Kapas Kabupaten Pesisir Selatan - Yoshi Indrayani; Hasbullah Malau (Jurusan Ilmu Administrasi Negara, 2019)
This study aims to determine and obtain description abaout implementation of Peraturan Nagari No 05 Tahun 2015 Tentang Penertiban Ternak Lepas di Kenagarian IV Koto Hilie Kecamatan Batang Kapas Kabupaten Pesisir Selatan aouthor also description abaouto stacles factors and efforts in dealing with the obstacles they face in implementation of the Pernag. This research is a descriptive research with qualitative naturalistic approach. The data used in this research sourced from primary and secondary data. Techniques used in data collection are interview and documentation. The informants in this study are choosen by purposive sampling. Analyzing data techniques are obtained through interviews and interpreted qualitatively throught abstract, words and statements. The result of this study indicates that the implementation of Peraturan Nagari No 05 Tahun 2015 Tentang Penertiban Ternak Lepas di Kenagarian IV Koto Hilie Kecamatan Batang Kapas Kabupaten Pesisir Selatan does no work optimallly. Implementation has 6 (six) indicators which is communication , resources, disposition, bureaucratic structure, consistency and clarity of purpose also socio-economic and technological condition of the community. Based on authors research result on implementation of Pernag there are found obstacle factors which is communication, resources, disposition, bureucratic structure and socio-economic condition of the community.